Elements of digital media in vocabulary remote-learning achievement - Yune Andryani Pinem; Andi Dian Rahmawan (Institute of Advanced Engineering and Science, 2023)
The urge of finding the most suitable method of remote teaching in a pandemic situation has become the center of recent studies. Equipped with instructional scaffolding, the absence of a teacher as a mentor in an asynchronous online class could be replaced by more interesting media for students’ self-study. This study was to look at games, songs, and a movie as media to enhance students’ achievement in English vocabulary. Further, elements in each media were observed along with students’ perceptions to explain the affected area in detail. This descriptive quantitative study used paired samples t-test toward students’ post-test scores of a control group (n=100) and an experimental group (n=100) in vocabulary. Students’ perception of taking media as learning tools in experimental class was measured in a questionnaire to explain the results. Results showed that the significantly experimental group outperformed in the final score. Trend on students’ perception in an experimental group toward these teaching media involved shared and specific features in media design, psychological and pedagogic elements. Further, it turned out that some primary and subsidiary features in games exceeded two other media (songs and movies) in vice versa generating some recommendations for future improvement.